The decision to flee: exploring gender-specific determinants of international refugee migration - Laura Renner; Lena Schmid (Journal of Population Economics, 2025)
While the determinants of refugee migration are well-studied, heterogeneities within the group of refugees have received little attention. In this paper, we use data on female and male refugee movements among African and Asian countries in the years 2002–2018 to explore gender differences in flight behavior along three dimensions: reasons for leaving, associated costs, and factors attracting individuals to specific asylum countries. Most prominently, our results show that women are more deterred than men by longer distances and flee significantly more often to neighboring countries. In addition, the number of battle-related fatalities increases male flows to neighboring countries significantly more than it increases female flows. We also find significant differences concerning the economic situation: extreme poverty has a larger impact on women whereas GDP per capita plays a more important role for male than for female flows.
Keywords: F22; O15; J16; 330; Refugees; International migration; Distance; Conflict; Gender